10x+7+2x=16x+7

Simple and best practice solution for 10x+7+2x=16x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x+7+2x=16x+7 equation:


Simplifying
10x + 7 + 2x = 16x + 7

Reorder the terms:
7 + 10x + 2x = 16x + 7

Combine like terms: 10x + 2x = 12x
7 + 12x = 16x + 7

Reorder the terms:
7 + 12x = 7 + 16x

Add '-7' to each side of the equation.
7 + -7 + 12x = 7 + -7 + 16x

Combine like terms: 7 + -7 = 0
0 + 12x = 7 + -7 + 16x
12x = 7 + -7 + 16x

Combine like terms: 7 + -7 = 0
12x = 0 + 16x
12x = 16x

Solving
12x = 16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16x' to each side of the equation.
12x + -16x = 16x + -16x

Combine like terms: 12x + -16x = -4x
-4x = 16x + -16x

Combine like terms: 16x + -16x = 0
-4x = 0

Divide each side by '-4'.
x = 0

Simplifying
x = 0

See similar equations:

| 2x-[3-5x(x-3)]=(2x-1)+10 | | (4-3(-2))x=-2x+2 | | x-7y=22 | | lnx-lnx(y-1)=1 | | x(4x-12)-7=-7 | | -2x+x^2+61y+4y^2=0 | | 6x+4y+3z=348 | | x^2+4y^2-2x+24y+37y=0 | | (2x-3)(2x-3)-16=-7 | | x(4x-12)=7 | | x(4x-12)-7=0 | | 5x^2+4sqrt(6)xy+7y^2-22=0 | | 2((-12+32)x-2)=56 | | 2((12+32)x-2)=56 | | 2((-12+4.8)x-2)=56 | | x^2+8x-13=0 | | (5x^3-2x)-(3+5x-2x^2-3x^3)= | | (2y^2-11xy+3x^2)-(4x^2+4y^2-10xy)= | | (9xy^2+4x^2y)-(x^2y-2xy^2)= | | (2+8x+4x^2)-(9+6x+2x^2)= | | (-2x^2+7x-1)-(8x^2-6x+5)= | | (x+5)(x+3)=28 | | (3x^2+4x+7)-(2x^2+6x-2)= | | (12-6x^2)-(4x^2-7)= | | x^2+2(m+1)+9m-5=0 | | 5e^4x=20 | | y=tan^6x | | (x-3)x^2=36 | | =5(4x-6+x^3)+5x(9-2x^2) | | =8p-2(7q-3p) | | X^4-3x^3-6x^2+3x+1=0 | | Iy=28 |

Equations solver categories